Physical Activity, Sedentary Behaviors, and Retinal Vascular Caliber in Children and Adolescents With Type 1 Diabetes. Issue 3 (May 2016) - Keel, Stuart; Itsiopoulos, Catherine; Koklanis, Konstandina; Vukicevic, Meri; Cameron, Fergus; Brazionis, Laima
Abstract : Purpose: The aim of this study was to investigate associations of physical activity and sedentary behaviors with retinal vascular caliber in children and adolescents with type 1 diabetes. Design: This was a hospital-based cross-sectional study. Methods: A study of 122 children and adolescents with type 1 diabetes was conducted over an 8-month period. Self-reported physical activity time and time spent watching TV or playing computer or video games were obtained using interviewer-administered questionnaires. Retinal vascular caliber was measured by a trained grader using a standardized protocol and later summarized as central retinal artery equivalent (CRAE) and central retinal vein equivalent (CRVE) using a semiautomated computer program. Results: After adjusting for confounders (age, sex, ethnicity, body mass index, systolic blood pressure, HbA1c, maternal smoking status, age at which cow's milk was introduced, and CRVE/CRAE, respectively), narrower CRAE was independently related to more time spent playing computer/video games [ExpB = −3.85; 95% confidence interval (CI), −6.41 to −1.29; P = 0.004], whereas wider CRVE was independently related to lower physical activity level (ExpB = −1.08; 95% CI, −2.01 to −0.15; P = 0.03) and more time spent playing computer/video games (ExpB = 4.72; 95% CI, 0.52–8.92; P = 0.02). Television viewing time was not associated with retinal vascular caliber after adjustment. Conclusions: The results of this study suggest that physical activity and sedentary behaviors in the form of "screen viewing time" are associated with retinal vessel caliber early in life. These results suggest that retinal vascular caliber may provide prognostic information beyond current traditional cardiovascular risk factors. Future longitudinal and interventional studies are warranted to evaluate the relevance of these observations.